The influence of visual aesthetic design and cross-cultural regions on virtual item purchase intentions in the genshin impact game - Dhia, Muhammad Rafi; Rijadi, Ciptaning Ndhika (Journal of Commerce, Management, and Tourism Studies, 2024)
This study examines how Visual Aesthetic Design and Cross-Cultural Region impact the intention to purchase virtual items in the game Genshin Impact. The independent variables are Visual Aesthetic Design and Cross-Cultural Region, while the dependent variable is Purchase Intention. Data was gathered using SPSS 20 by distributing a questionnaire to 96 active players from Indonesia, aged 18-35, who have been playing Genshin Impact for at least 3 months. The research uses a quantitative associative approach with primary data and non-probability purposive sampling. The results show that Visual Aesthetic Design has a positive and significant effect on Purchase Intention, evidenced by a t-count of 3.486 (exceeding the t-table value of 1.661) and a significance level of 0.01 (below 0.05). Likewise, Cross-Cultural Region has a positive and significant impact on Purchase Intention, with a t-count of 5.576 (greater than the t-table value of 1.661) and a significance level of 0.00 (below 0.05). The combined effect of both Visual Aesthetic Design and Cross-Cultural Region on Purchase Intention is significant, as indicated by an F-count of 70.984 (surpassing the F-table value of 3.09) and a significance level of 0.00 (below 0.05).